Послесловие. P. S.: стихи, поэмы, басни / Олег Кузьмин - Кузьмин Олег Анатольевич (Удмуртия, 2008)
Экземпляры: Аб (20160408) / Инвентарный номер: 104029 / Цена: 60.00 / Авт.знак: К 89 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6